The representation of Reog Ponorogo’s character construction in Marjan’s beverage product advertisement - Wijaya, Rizki Ardiatama; Suryana, Asep; Syuderajat, Fajar (Universitas Padjadjaran, 2025)
Background: This research was motivated by the different approaches taken in Marjan’s advertisement for Ramadan 2021 compared to previous years. Marjan is known for always showcasing local Indonesian culture explicitly in its advertisements so that the culture presented is identical to the original. In 2021, Marjan presented Reog Ponorogo with a superhero fantasy story, so Reog Ponorogo was implicitly displayed in the advertisement. Purpose: This research aims to determine the representation of the Reog Ponorogo character construction in Marjan’s Ramadan 2021 advertisement. Methods: This research uses a qualitative method with Peirce’s triadic semiotic analytic approach. Results: The representation of Reog Ponorogo construction characters in the Marjan advertisement for Ramadan 2021 was evident in the signs that represent Reog Ponorogo. Marjan’s advertisement constructs the concept of fusing traditional culture with modern popular culture. Conclusions: The resulting fusion creates an advertisement that tells a superhero fantasy story but still carries the identity of Reog Ponorogo. The media construction is built to keep Marjan’s advertisement relevant to the product’s target market, with a message of unity and heroism that differs from its traditional counterpart. Implication: The presentation of traditional culture in media should be done with the utmost care so as not to conflict with the culture’s traditional origin. Consumers are expected to start by getting to know the local culture inherent in themselves so that when this culture is presented in media, consumers can evaluate the media’s presentation of culture in the created content.